THE IMPORTANCE OF HUMAN SPIRIT AND CONSCIOUSNESS IN THE SOCIALIZATION OF THE PERSON (Universal International Scientific Journal, 2026)
For thousands of years, humanity has sought to explore the secrets of the universe,but the greatest and yet unsolved mystery still lies within ourselves - in our psyche.Why are we so unreasonably afraid of certain things? Why do some memories fade away, while others remain imprinted for life? To find answers to these questions, we need to understand the delicate line between the human psyche and consciousness.
Keywords: psyche; psychology; critical thinking